News Presentation of Contemporary Events: Opinion and Clichés or Expanding Public Understanding of the World - Gamji, Musa Bara’u; Nasidi, Qaribu Yahaya; Sani, Almansur Ado (NIU Journal of Social Sciences, 2018)
The argument whether news presents opinions and clichés about contemporary events and not educating or expanding public understanding of the world, has to be based on the concept of news and its values. Academically, journalists were seeing as reporting event in a way that misrepresents a specific group in a certain society, and some pessimistic critical academics that have justified this standard are slipping and that the quality of news is declining. Confronting the views of academics about the News and journalism practitioners, responded that news is a first draft of history, which is also an ability to provide both a truthful and objective contemporary account. This paper assessed the influence of news presentation on public knowledge of news events, opinion and clichés in Nigeria. Arguably, journalist can turn everything into clichés and opinion when they are operating under a certain constrain such as censorship. Presentation of opinions and clichés in the news media can also be attributed to the changing pattern of news consumption. If news can be an orientation towards the truth and through truthful accounts of contemporary events, to be presented via journalistic way with accuracy and sincerity, being impartial, balanced and objective or informing people about something that just happened, and needs to be balanced in an accurate and honest information to the interest of the public, then it should be impartial and objective with a view to educating and expanding public understanding about contemporary events. Keywords :  Clichés, Contemporary events, Education, Media, News, Opinion, Public